Post-earthquake emotional and behavioral problems in children: parent experiences, coping strategies, and predictive factors - Tunç, Yunus; Çelik, Osman Tayyar; Kaçmaz, Cihangir (Frontiers in Psychology, 2026)
ObjectiveIn this study, the emotional and behavioral problems observed in children aged 6–11 years following the Kahramanmaras earthquakes in Türkiye on February 6, 2023, have been examined based on parental experiences, and it has been investigated whether the psychological resilience and warmth of the parents could predict these problems.MethodsThe study was conducted using an explanatory sequential mixed-methods design. Fifty-five parents met the inclusion criteria for the qualitative phase, while 398 parents participated in the quantitative phase. Participants were identified using convenience and snowball sampling methods. Content analysis was applied to the qualitative data, while the quantitative data underwent analysis through descriptive statistics, T-tests, ANOVA, correlation studies, and hierarchical linear regression. In the quantitative phase, the Emotional and Behavioral Problems Questionnaire, the Brief Resilience Scale (BRS), and the Parent Acceptance-Rejection Questionnaire (PARQ) warmth/affection subscale were used.ResultsThe study revealed that, according to parents' perceptions, children's emotional problems after the earthquake revealed themselves with symptoms such as loneliness, constant anxiety about the earthquake, and fear of the dark, and parents reported various behavioral problems with their children. Parents tackled these issues by demonstrating resilience, warmth, protective actions, and trust-building. The quantitative research revealed substantial evidence of these issues' prevalence in children and the influence of parental factors and family dynamics.ConclusionIt was determined that parental psychological resilience is a key factor in predicting parents' reported emotional and behavioral problems for children, unlike parental warmth. Moreover, aspects such as household income and the number of siblings were also linked to parents' reported emotional and behavioral problems for children. The study thus provides a comprehensive framework for appreciating and aiding children's emotional and behavioral responses.